Zdravljenje preležanin - Šavrin, Rajmond (Rehabilitacija (Ljubljana), 2010)
Pressure sores are among the most frequent and life-threatening complications in people with spinal cord injury. Treatment is costly and long-lasting, so many investigators have been trying to find the best treatment method for decades. Various treatment methods are known, including various physical and surgical ones, and prevention is also important. We summarise recent scientific research on the use of various methods of pressure sore treatment and their efficiency. Although the majority of the articles report observable improvement in pressure sore healing, the overall level of scientific evidence is still low.
Keywords: preležanine; rane; therapy; zdravljenje